Continuous Dural Suturing for the Closure of Grade 1 to 2 Cerebrospinal Fluid Leakage After Pituitary Adenoma Removal Using an Endoscopic Endonasal Approach. Issue 2 (15th March 2023) - Zhou, Lv; Wang, Bin; Ye, Lei; Gao, Peng; Cheng, Hongwei
Abstract : In this study, we aim at evaluating continuous dural suturing in patients with grade 1 to 2 cerebrospinal fluid (CSF) leakage after pituitary adenoma removal using an endoscopic endonasal approach. The study population comprised 381 pituitary adenoma patients who underwent endoscopic endonasal removal of the tumor. The degree of intraoperative CSF leakage was graded based on Esposito method. Cranial base repair using continuous dural suturing was performed according to the grade of CSF leakage. Intraoperative grade 1 to 2 CSF leakage was identified in 143 patients (37.5%). Continuous dural suturing to repair the cranial base was accepted by 61 patients and refused by 82 patients. Among patients who accepted dural suturing, the incidence of postoperative CSF leakage was reduced and the length of hospital stay was shortened. Patients with low-flow leakage were treated using a reduced vascularized pedicled nasoseptal flap. In conclusion, our graded cranial base repair method using the dural suturing technique is simple and effective.